Integrasi Protokol Sinkronisasi Waktu Reference Broadcast Synchronization (RBS) dan Pengiriman Data Flooding pada Wireless Sensor Node - Zhafran Wadiansyah; Sabriansyah Rizqika Akbar; Edita Rosana Widasari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Nowdays, technology is already evolve and help human in terms of obatining information. One of the technology that being concern is Wireless Sensor Network (WSN). WSN is a wireless sensor network consisting of multiple nodes connected in one network. WSN technology has several delivery protocols one of which is Flooding Routing. Flooding is sending data by flooding the network with data to be sent.The problems that occur from Flooding is the occurrence a lot of data redundancy that will meet the network.Another problem facing the collision of data at the time of delivery due to local time difference. Therefore there will be data collisions that render the data unacceptable. In this research the author will solve the problems that occur in data transmission in WSN and Flooding by integrating the synchronization reference time synchronization instruction protocol and data flooding transmission. This system will schedule the sending of data to be sent. To support the scheduling the local time of each node must be the same. Therefore, the reference broadcast synchronization protocol is chosen as time synchronization between nodes. Furthermore, scheduling the delivery using Time Division Multiple Access method.Time synchronization and data transmission scheduling will be applied for the delivery of flooding data. Based on the result, each node on the WSN network is able to synchronize its timing according to the RBS method. Furthermore, the scheduling with TDMA method is also capable of being applied. So, between nodes can send data in accordance with the schedule that has been given. The system also capable of implementing the flooding protocol well. Node beacons are also able to overcome the problem of data redundancy that occurs by providing a header on every packet sent. The average packet delivery delay using flood is 1869.2 micro seconds.